Academic Burnout: The Role of Mindful Parenting in Overcoming Burnout in Madrasah - Amaliya Dewi Rasyida; Muhammad Munif; Ummi Puji Astutik; Moh Syamsul Hadi (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
This study aims to analyze the role of mindful parenting in overcoming academic burnout at MI Nurul Mun'im in learning Islamic Religious Education under the auspices of the Nurul Jadid Paiton Probolinggo Islamic Boarding School. The technique used in collecting data is interview and observation. This descriptive study uses a qualitative approach to the literature study method. To get an overview of academic burnout, especially in learning Islamic religious education. This study's subject is the teacher care pattern in increasing learning motivation. Interviews were conducted with homeroom teachers, PAI teachers, counselling teachers and students. The results of the study show that the role of mindful parenting in overcoming academic burnout can be carried out in the learning process, which includes role theory according to Biddle and Thomas, in which there are four roles, namely: The subject of the interaction, The behaviour that appears in the exchange, The position of people in behaviour, The link between people and behaviour. This research has implications that teachers must have innovation and creativity in managing their learning by the specified targets to be able to generate motivation and create fun classroom learning as well as the intelligence of students as a whole.